"Cerrado" cashew (Anacardium othonianum Rizz.) juice improves metabolic parameters in women: A pilot study. (June 2020) - Silva, Andriely Lucas Lima e; Santos, Daiane Costa dos; Sousa, Tainara Leal de; Silva, Fabiano Guimarães; Egea, Mariana Buranelo
Graphical abstract: Highlights: "Cerrado" cashew pseudofruit produce juice with high vitamin C content. The 4-weeks ingestion of "Cerrado" cashew juice improves lipid profile of women. The arterial BP-lowering of women occurred with "Cerrado" cashew juice ingestion. The time of glucose peak increased 33% after 30 days-ingestion "Cerrado" cashew. Abstract: This study aimed to evaluate the impact of 30-day "Cerrado" cashew juice consumption in women. "Cerrado" cashew juice was produced through enzymatic clarification after maceration of Anacardium othonianum pseudofruit. The "Cerrado" cashew juice was clarified, pasteurized, and evaluated for its chemical characteristics, and a daily intake of 400 mL was used in the pilot study of nine women. The "Cerrado" cashew juice showed high vitamin C content (30 mg 100 mL −1 ), and consumption of "Cerrado" cashew juice increases the recommended daily intake of manganese (56 %), zinc (22 %), iron (14 %), and copper (13 %). Consumption of "Cerrado" cashew juice improved the time to reach the maximum glucose value in the glycemic curve, the cholesterol levels (triglycerides, total and low-density lipoprotein cholesterol) and systolic blood pressure in women.